Comparison of the Directigen Flu A+B Membrane Enzyme Immunoassay with Viral Culture for Rapid Detection of Influenza A and B Viruses in Respiratory Specimens - Cazacu, Andreea C. (American Society for Microbiology, 2004)
The performance of a commercially available, rapid membrane enzyme immunoassay for influenza A and B virus detection was compared to that of viral culture in 4,092 respiratory specimens collected from patients presenting with respiratory symptoms during the 2002-2003 influenza season. The test's overall sensitivity was 43.83%, lower than previously reported but similar for detection of both influenza A and B viruses (42.98 versus 44.76%). However, specificity, 99.74%, was excellent for both influenza A and B viruses (99.82 versus 99.92%). These values make this test a very good confirmatory test when clinical suspicion is high, but a less accurate screening test for large populations.